KEEFEKTIFAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN HASIL BLAJAR IPA SISWA KELAS VI SD NEGERI 011 AIR EMAS - Sutiyem Sutiyem (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Cooperative learning type integrated cooperative reading and composition is a comprehensive program that can be used in learning, especially in science learning. the aim was to improve students' learning outcomes in science class VI Elementary School 011 Air Emas. The results showed, at the base score the average score of students was only 64, after improvement in the first cycle using a cooperative model of integrated cooperative reading and composition (CIRC) type, the average value increased to 78, and in cycle II it increased to 86. These results prove that, the model of integrated cooperative reading and composition (CIRC) proved to be effective in improving the process and student learning outcomes